Synthesis of a Versatile Building Block for the Preparation of 6-N-Derivatized α-Galactosyl Ceramides: Rapid Access to Biologically Active Glycolipids - Jervis, Peter J. (American Chemical Society, 2010)
[Image: see text] A concise route to the 6-azido-6-deoxy-α-galactosyl-phytosphingosine derivative 9 is reported. Orthogonal protection of the two amino groups allows elaboration of 9 into a range of 6-N-derivatized α-galactosyl ceramides by late-stage introduction of the acyl chain of the ceramide and the 6-N-group in the sugar headgroup. Biologically active glycolipids 6 and 8 have been synthesized to illustrate the applicability of the approach.